High-conductivity hard carbon composite material and preparation method and application thereof
Highly conductive hard carbon composite materials prepared through steps such as pre-oxidation, pre-carbonization and high-temperature carbonization solve the problem of insufficient conductivity of hard carbon materials and achieve effective applications in high-energy-density and high-power-density batteries.
Patent Information
- Application Number
- CN202411634427.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-24
AI Technical Summary
Hard carbon materials face problems of insufficient conductivity and poor rate performance in practical applications, which limits their application potential in high-energy and high-power density batteries.
By pre-oxidizing and pulverizing the hard carbon precursor in an air atmosphere, then pre-carbonizing it in an inert atmosphere, then mixing and grinding it with a dispersant, carbon nanotube slurry, binder and solvent, and finally performing high-temperature carbonization in an inert atmosphere. Preparation of highly conductive hard carbon composite materials.
This method is simple to operate, low in cost, easy to produce on a large scale, and significantly improves the conductivity of hard carbon anode materials while maintaining its high capacity and cycle stability.
Smart Images

Figure CN119349553A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material chemistry, and in particular to a high-conductivity hard carbon composite material and a preparation method and application thereof. Background Art
[0002] Hard carbon materials are considered to be a better choice to replace traditional graphite negative electrode materials due to their unique structure and properties. They not only have a high specific capacity, but also show good cycle stability and low cost advantages. However, the problems of insufficient conductivity and poor rate performance faced by hard carbon materials in practical applications have become a bottleneck restricting their further development. The existence of these problems limits the application potential of hard carbon materials in high energy density and high power density batteries.
[0003] To solve these problems, researchers have tried a variety of methods, including doping with metal elements, introducing conductive carbon networks, etc. Although these methods have improved the conductivity of hard carbon materials to a certain extent, they have also brought new challenges such as rising costs, complex processes, and capacity loss.
[0004] Therefore, developing a method that can significantly improve the conductivity of hard carbon negative electrode materials while maintaining their high capacity and cycle stability is of great significance for the commercialization and widespread application of battery technology.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a high-conductivity hard carbon composite material and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a method for preparing a high-conductivity hard carbon composite material, comprising the following steps:
[0009] Pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor;
[0010] The pre-oxidized precursor is crushed and then pre-carbonized in an inert atmosphere to obtain a pre-carbonized precursor;
[0011] The pre-carbonized precursor is mixed with a dispersant, a carbon nanotube slurry, a binder and a solvent, and then ground to obtain black liquor;
[0012] After the black liquor is dried, it is carbonized at high temperature in an inert atmosphere to obtain a high-conductivity hard carbon composite material.
[0013] In an optional embodiment, the hard carbon precursor includes at least one of a biomass-based precursor, a polymer-based precursor, and a coal-based precursor;
[0014] And / or, the binder includes at least one of a biomass-based binder and a polymer-based binder.
[0015] In an alternative embodiment, the polymer-based precursor includes a resin-based precursor.
[0016] In an alternative embodiment, the resin-based precursor includes at least one of a phenolic resin and an epoxy resin.
[0017] In an alternative embodiment, the coal-based precursor includes at least one of anthracite, coal tar pitch, and lignite.
[0018] In an alternative embodiment, the biomass-based precursor comprises at least one of a bio-precursor, a sugar-based precursor, and a starch-based precursor.
[0019] In an optional embodiment, the pre-oxidation temperature is 150° C. to 280° C., and the pre-oxidation time is 6 h to 12 h.
[0020] In an optional embodiment, the pre-oxidation temperature is 220° C., and the pre-oxidation time is 12 hours.
[0021] In an optional embodiment, the pre-carbonization temperature is 500° C. to 900° C., and the pre-carbonization time is 1 h to 6 h.
[0022] In an optional embodiment, the pre-carbonization temperature is 800° C., and the pre-carbonization time is 3 hours.
[0023] In an optional embodiment, the mass ratio of the pre-carbonized precursor, the dispersant, the carbon nanotube slurry and the binder is (95-99):(0.5-1):(0.5-5):(0.5-5).
[0024] In an optional embodiment, the grinding speed is 700Rpm to 1600rpm, and the grinding time is 0.2h to 3h.
[0025] In an optional embodiment, the grinding speed is 1200 rpm and the grinding time is 0.5 h.
[0026] In an optional embodiment, the drying method includes at least one of freeze drying, spray drying, fluidized bed drying and flash drying.
[0027] In an alternative embodiment, the drying method is freeze-drying.
[0028] In an optional embodiment, the temperature of high temperature carbonization is 1000° C. to 1600° C., and the time of high temperature carbonization is 1 h to 6 h.
[0029] In an optional embodiment, the temperature of high temperature carbonization is 1300° C., and the time of high temperature carbonization is 3 hours.
[0030] In a second aspect, the present invention provides a high-conductivity hard carbon composite material prepared by the preparation method of any one of the aforementioned embodiments.
[0031] In a third aspect, the present invention provides a use of the highly conductive hard carbon composite material according to the aforementioned embodiment in a supercapacitor, a battery or an electromagnetic shielding material.
[0032] The beneficial effects of the present invention include:
[0033] The preparation method of the high-conductivity hard carbon composite material provided by the present invention is simple to operate, low in cost, and easy to mass produce. It can not only significantly improve the conductivity of the hard carbon negative electrode material, but also maintain its high capacity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 This is a SEM image of the high-conductivity hard carbon composite material obtained in Example 1;
[0036] Figure 2 This is a SEM image of the high-conductivity hard carbon composite material obtained in Example 5;
[0037] Figure 3 for Figure 2 A partial enlarged view of the
[0038] Figure 4 The conductivity of the high-conductivity hard carbon composite material obtained in Examples 4 to 6 and Comparative Example 1 varies with pressure;
[0039] Figure 5 The graph of compaction density versus pressure of the high-conductivity hard carbon composite material obtained in Examples 4 to 6 and Comparative Example 1;
[0040] Figure 6 Graph showing the cycle performance of the highly conductive hard carbon composite material obtained in Examples 4 to 6;
[0041] Figure 7 Graph showing the voltage distribution of the highly conductive hard carbon composite material obtained in Examples 4 to 6. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0043] The highly conductive hard carbon composite material provided by the present invention and its preparation method and application are described in detail below.
[0044] The present invention provides a method for preparing a high-conductivity hard carbon composite material, comprising the following steps:
[0045] S1: pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor.
[0046] The hard carbon precursor may include at least one of a biomass-based precursor, a polymer-based precursor and a coal-based precursor. Among them, the biomass-based precursor may exemplarily but not limitatively include at least one of a sugar-based precursor (such as glucose, xylose and sucrose, etc.), a starch-based precursor (such as corn starch, potato starch, wheat starch and rice starch, etc.) and a biological precursor (such as roots, stems, leaves, flowers and fruits, etc.). The polymer-based precursor may include a resin-based precursor, such as at least one of a phenolic resin and an epoxy resin. The coal-based precursor may include at least one of anthracite, coal tar and lignite.
[0047] In some optional embodiments, the pre-oxidation temperature can be 150°C to 280°C, such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C, etc., or other values within the range of 150°C to 280°C.
[0048] The pre-oxidation time can be 6 h to 12 h, such as 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc., or other values within the range of 6 h to 12 h.
[0049] In some typical embodiments, the pre-oxidation temperature is 220° C. and the pre-oxidation time is 12 hours.
[0050] By pre-oxidizing the hard carbon precursor, the oxygen content of the hard carbon precursor can be increased, and graphitization can be inhibited during the carbonization process, which is beneficial to regulating the growth of carbon microcrystals.
[0051] S2: crushing the pre-oxidized precursor and then pre-carbonizing it in an inert atmosphere to obtain a pre-carbonized precursor.
[0052] In some optional embodiments, the pre-oxidized precursor may be crushed to a particle size D 50 It is about 30μm to 50μm.
[0053] In some optional embodiments, the inert atmosphere may be, for example, a nitrogen atmosphere or an argon atmosphere.
[0054] In some optional embodiments, the pre-carbonization temperature can be 500°C to 900°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, or other values within the range of 500°C to 900°C.
[0055] The pre-carbonization time may be 1 h to 6 h, such as 1 h, 2 h, 3 h, 4 h, 5 h or 6 h, etc., or may be other values within the range of 1 h to 6 h.
[0056] In some typical implementations, the pre-carbonization temperature is 800° C. and the pre-carbonization time is 3 hours.
[0057] By pre-carbonizing the pre-oxidized precursor, the pre-oxidized precursor can be decarbonized in advance and small molecules can be removed, which is beneficial to improve the yield and reduce energy consumption. In addition, the precursor obtained in this process can be crushed to expose more fresh surfaces, and the exposed interface can be re-carbonized in the subsequent process, which is beneficial to improve the coulombic efficiency of the battery prepared therefrom.
[0058] S3: mixing the pre-carbonized precursor with a dispersant, a carbon nanotube slurry, a binder and a solvent and grinding the mixture to obtain black liquor.
[0059] The dispersant may illustratively but not limitatively include at least one of polyvinyl pyrrolidone, ethanolamine, polyethylene glycol and carboxylic acid cellulose.
[0060] The binder may include at least one of a biomass-based binder and a polymer-based binder. The biomass-based binder may exemplarily but not limitatively include at least one of glucose, xylose and sodium alginate. The polymer-based binder may exemplarily but not limitatively include at least one of sodium cellulose carboxylate and styrene-butadiene rubber.
[0061] The solvent may illustratively but not limitatively include at least one of water and ethanol.
[0062] The mass percentage of carbon nanotubes in the carbon nanotube slurry may be 3% to 8%.
[0063] In some optional embodiments, the mass ratio of pre-carbonized precursor, dispersant, carbon nanotube slurry and binder can be (95-99):(0.5-1):(0.5-5):(0.5-5), such as 95:0.5:0.5:4, 95:0.5:3:1.5, 95:0.5:4:0.5, 95:1:0.5:3.5, 95:1:2:2, 95:1:1:3, 97:0.5:2:0.5 or 97:1:1:3, etc.
[0064] It should be noted that although the addition of carbon nanotube slurry can enhance the conductivity of hard carbon composite materials, it will reduce the first coulomb efficiency of the material to a certain extent, which may be related to the increase in the specific surface area leading to the increase in the formation of solid electrolyte interface (SEI) film. Therefore, the amount of carbon nanotube slurry added needs to be controlled within an appropriate range to balance the ionic conductivity and electronic conductivity of the hard carbon composite material, thereby obtaining better electrochemical performance.
[0065] In some optional embodiments, the grinding speed is 700 rpm to 1600 rpm, such as 700 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm or 1600 rpm, etc. The grinding time can be 0.2 h to 3, such as 0.2 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.
[0066] In some optional embodiments, the grinding speed is 1200 rpm and the grinding time is 0.5 h.
[0067] It should be noted that the speed and time during the grinding process have a significant impact on the material properties, which is mainly reflected in the regulation of particle size and the aspect ratio of carbon nanotubes. If the grinding speed is too low or the grinding time is too short, it is easy to cause the carbon particles to be too large, affecting the electrode production and the dispersion of carbon tubes. If the grinding speed is too high or the grinding time is too long, it is easy to cause the carbon particles to be too small, affecting the material's tap density; and reducing the aspect ratio of carbon tubes.
[0068] S4: After the black liquor is dried, it is carbonized at high temperature in an inert atmosphere to obtain a highly conductive hard carbon composite material.
[0069] In some optional embodiments, the drying method may illustratively but not limitatively include at least one of freeze drying, spray drying, fluidized bed drying and flash drying. In some more typical embodiments, the drying method is freeze drying.
[0070] In some optional embodiments, the temperature of high temperature carbonization may be 1000°C to 1600°C, such as 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, or other values within the range of 1000°C to 1600°C.
[0071] The high temperature carbonization time may be 1 h to 6 h, such as 1 h, 2 h, 3 h, 4 h, 5 h or 6 h, etc., or may be other values within the range of 1 h to 6 h.
[0072] In some typical implementations, the high temperature carbonization temperature is 1300° C., and the high temperature carbonization time is 3 hours.
[0073] As mentioned above, by obtaining different solutions within the range of conditions provided by the present invention, the conductivity, pore structure and surface properties of the composite material can be adjusted to meet the needs of different applications. The preparation method is simple to operate, low in cost, and easy to scale up, which can significantly improve the conductivity of the hard carbon negative electrode material while maintaining its high capacity and cycle stability.
[0074] Correspondingly, the present invention also provides a high-conductivity hard carbon composite material, which is prepared by the above preparation method.
[0075] The obtained highly conductive hard carbon composite material has a three-dimensional network structure.
[0076] In some typical embodiments, in the high-conductivity hard carbon composite material, the carbon nanotubes are evenly distributed on the surface of the hard carbon particles, and the hard carbon is in the form of irregular particles.
[0077] In a third aspect, the present invention also provides an application of the above-mentioned high-conductivity hard carbon composite material in supercapacitors, batteries or electromagnetic shielding materials.
[0078] Exemplarily, the highly conductive hard carbon composite material can be used to prepare alkali metal secondary batteries, such as sodium ion batteries.
[0079] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0080] Example 1
[0081] This embodiment provides a highly conductive hard carbon composite material, and the preparation method thereof is as follows:
[0082] S1: pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor.
[0083] The hard carbon precursor is glucose, the pre-oxidation temperature is 220°C, and the pre-oxidation time is 12 h.
[0084] S2: The pre-oxidized precursor is crushed into a particle size D using a grinder. 50 The particle size is about 50 μm, and then pre-carbonized in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a pre-carbonized precursor (black block).
[0085] The pre-carbonization temperature is 800°C and the pre-carbonization time is 3h.
[0086] S3: The pre-carbonized precursor is coarsely ground with a grinder to obtain a coarse powder (particle size D 50 The coarse powder is then mixed with a dispersant, a carbon nanotube slurry, a binder and a solvent and ground to obtain black liquor.
[0087] The dispersant is polyvinyl pyrrolidone, the concentration of carbon nanotubes in the carbon nanotube slurry is 5wt%, the binder is glucose, and the solvent is water. The mass ratio of the coarse powder, the dispersant, the carbon nanotube slurry and the binder is 98:0.5:0.5:1, and the amount of the solvent is calculated based on a solid-liquid ratio of 15%.
[0088] The grinding was carried out using a sand mill at a rotation speed of 1200 rpm for 0.5 h.
[0089] S4: After the black liquor is dried, it is carbonized at high temperature in a nitrogen atmosphere to obtain a highly conductive hard carbon composite material.
[0090] The drying is carried out by freeze drying, and loose black powder is obtained after the process.
[0091] The temperature of high temperature carbonization is 1300°C, and the time of high temperature carbonization is 3h.
[0092] Example 2
[0093] The difference between this embodiment and embodiment 1 is that the mass ratio of the coarse powder, the dispersant, the carbon nanotube slurry and the binder is 97.5:0.5:1:1.
[0094] Example 3
[0095] The difference between this embodiment and embodiment 1 is that the mass ratio of the coarse powder, the dispersant, the carbon nanotube slurry and the binder is 96.5:0.5:2:1.
[0096] Example 4
[0097] The difference between this embodiment and embodiment 1 is that the hard carbon precursor is corn starch.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 2 is that the hard carbon precursor is corn starch.
[0100] Example 6
[0101] The difference between this embodiment and embodiment 3 is that the hard carbon precursor is corn starch.
[0102] Example 7
[0103] The difference between this embodiment and embodiment 5 is that the hard carbon precursor is straw.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 5 is that the hard carbon precursor is a resin (specifically a phenolic resin).
[0106] Example 9
[0107] The difference between this embodiment and embodiment 5 is that the hard carbon precursor is bamboo powder.
[0108] Example 10
[0109] This embodiment provides a highly conductive hard carbon composite material, and the preparation method thereof is as follows:
[0110] S1: pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor.
[0111] The hard carbon precursor is glucose, the pre-oxidation temperature is 150°C, and the pre-oxidation time is 12h.
[0112] S2: The pre-oxidized precursor is crushed into a particle size of D using a grinder. 50 The particle size is about 30 μm, and then pre-carbonized in an argon atmosphere and naturally cooled to room temperature to obtain a pre-carbonized precursor (black block).
[0113] The pre-carbonization temperature is 500°C and the pre-carbonization time is 6 hours.
[0114] S3: The pre-carbonized precursor is coarsely ground with a grinder to obtain coarse powder (with a particle size of about 30 μm). The coarse powder is then mixed with a dispersant, a carbon nanotube slurry, a binder and a solvent and then ground to obtain black liquor.
[0115] The dispersant is carboxylic acid cellulose, the concentration of carbon nanotubes in the carbon nanotube slurry is 3wt%, the binder is glucose, and the solvent is water. The mass ratio of the coarse powder, the dispersant, the carbon nanotube slurry and the binder is 95:0.5:4:0.5, and the amount of the solvent is calculated based on a solid-liquid ratio of 15%.
[0116] The grinding was carried out using a sand mill at a rotation speed of 1200 rpm for 0.5 h.
[0117] S4: After the black liquor is dried, it is carbonized at high temperature in an argon atmosphere to obtain a highly conductive hard carbon composite material.
[0118] The drying is carried out by spray drying, and loose black powder is obtained after the treatment.
[0119] The temperature of high temperature carbonization is 1000°C, and the time of high temperature carbonization is 6 hours.
[0120] Embodiment 11
[0121] This embodiment provides a highly conductive hard carbon composite material, and the preparation method thereof is as follows:
[0122] S1: pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor.
[0123] The hard carbon precursor is sucrose, the pre-oxidation temperature is 280°C, and the pre-oxidation time is 6 hours.
[0124] S2: The pre-oxidized precursor is crushed into a particle size of D using a grinder. 50 The particle size is about 40 μm, and then pre-carbonized in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a pre-carbonized precursor (black block).
[0125] The pre-carbonization temperature is 900°C and the pre-carbonization time is 1 h.
[0126] S3: The pre-carbonized precursor is coarsely ground with a grinder to obtain coarse powder (with a particle size of about 30 μm). The coarse powder is then mixed with a dispersant, a carbon nanotube slurry, a binder and a solvent and then ground to obtain black liquor.
[0127] The dispersant is polyethylene glycol, the concentration of carbon nanotubes in the carbon nanotube slurry is 8wt%, the binder is glucose, and the solvent is water. The mass ratio of the coarse powder, the dispersant, the carbon nanotube slurry and the binder is 98:0.5:1:0.5, and the amount of the solvent is calculated based on a solid-liquid ratio of 15%.
[0128] The grinding was carried out using a sand mill at a rotation speed of 1200 rpm for 0.5 h.
[0129] S4: After the black liquor is dried, it is carbonized at high temperature in a nitrogen atmosphere to obtain a highly conductive hard carbon composite material.
[0130] The drying is carried out in a fluidized bed drying manner, and loose black powder is obtained after the treatment.
[0131] The temperature of high temperature carbonization is 1600°C, and the time of high temperature carbonization is 1h.
[0132] Comparative Example 1
[0133] The difference between this comparative example and Example 5 is that no carbon nanotubes are added to the material ratio of S3.
[0134] Comparative Example 2
[0135] The difference between this comparative example and Example 5 is that the grinding speed in S3 is 1400 rpm.
[0136] Comparative Example 3
[0137] The difference between this comparative example and Example 5 is that the grinding time in S3 is 1 h.
[0138] Test example
[0139] ① Taking the high conductive hard carbon composite materials prepared in Example 1 and Example 5 as an example, scanning electron microscopy was performed, and the results are as follows: Figures 1 to 3 shown.
[0140] Depend on Figure 1 It can be seen that in the high-conductivity hard carbon composite material obtained in Example 1, the carbon nanotubes are evenly distributed on the surface of the hard carbon particles, and the hard carbon is in an irregular particle shape.
[0141] Depend on Figure 2 and Figure 3 It can be seen that in the high-conductivity hard carbon composite material obtained in Example 5, the carbon nanotubes are evenly distributed on the surface of the hard carbon particles, and the hard carbon is in irregular particle shape.
[0142] ② Taking the high conductive hard carbon composite materials prepared in Examples 4 to 6 and Comparative Example 1 as examples, the conductivity and compaction density of the materials were tested using a powder conductivity meter. The results are as follows: Figure 4 and Figure 5 shown.
[0143] Depend on Figure 4 It can be seen that the electrical conductivity of the high-conductivity hard carbon composite material increases with the increase of carbon nanotube material, and the conductivity becomes better and better.
[0144] Depend on Figure 5 It can be seen that the compaction density of the high conductive hard carbon composite material increases with the increase of carbon nanotube material.
[0145] ③. Taking the high-conductivity hard carbon composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 3 as examples, with metallic sodium as the negative electrode, the high-conductivity hard carbon composite materials obtained in each Example and Comparative Example as the positive electrode, they were assembled into 2016-type simulated batteries to verify the sodium storage performance of the materials. The results are as follows: Figure 6 and Figure 7 (corresponding to Examples 4 to 6) and shown in Table 1.
[0146] Table 1 Electrochemical test results
[0147]
[0148]
[0149] A. By Figure 6 and Figure 7 It can be seen that the first cycle coulombic efficiency of the high conductive hard carbon composite material decreases with the increase of carbon tube material, which may be related to the specific surface area of the material. Adding 1wt% carbon tube is a more suitable ratio, and the reversible capacity is more than 266mAh / g after 90 cycles at 0.2C.
[0150] B. As can be seen from Table 1, the results of Examples 1 to 11 prove that the modification strategy of the present invention is generally applicable to sugar-based, starch-based, resin-based and biomass-based hard carbon precursors. Figures 1 to 3 The SEM image clearly reveals that carbon nanotubes are evenly distributed on the surface of the material, building an efficient three-dimensional conductive network. Figure 4 Compared with comparative example 1, as the content of carbon nanotube material increases, the conductivity of the high-conductivity hard carbon composite material is significantly improved. Figure 5 Compared with Comparative Example 1, as the content of carbon nanotube material increases, the compaction density of the high conductive hard carbon composite material also increases, which is most likely attributed to the uniform distribution of carbon nanotubes, which effectively achieves the filling of fine voids.
[0151] However, the electrochemical test results show that the introduction of carbon nanotubes reduces the first coulomb efficiency of the material to a certain extent, which may be related to the increase in specific surface area leading to the increased formation of solid electrolyte interface (SEI) film. Taking all factors into consideration, although adding carbon nanotubes in appropriate amounts can enhance the conductivity of the material, experiments show that 1wt% of carbon nanotubes are more superior in electrochemical performance. This phenomenon may reflect the decisive step effect between electronic conductivity and ionic conductivity of the material.
[0152] In addition, it can be seen from Example 5 and Comparisons 2 to 3 that the rotation speed and time during the grinding process also have a significant impact on the properties of the hard carbon composite material, mainly reflected in the regulation of particle size and aspect ratio of carbon nanotubes, which is crucial for optimizing material properties.
[0153] In summary, by obtaining different solutions within the range of conditions provided by the present invention, the conductivity, pore structure and surface properties of the composite material can be adjusted to meet the needs of different applications. The preparation method is simple to operate, low in cost, and easy to scale up, which can significantly improve the conductivity of the hard carbon negative electrode material while maintaining its high capacity and cycle stability.
[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly conductive hard carbon composite material, characterized in that: The following steps are involved: Pre-oxidizing the hard carbon precursor in an air atmosphere to obtain a pre-oxidized precursor; The pre-oxidized precursor is crushed and then pre-carbonized under an inert atmosphere to obtain a pre-carbonized precursor; The pre-carbonized precursor is mixed with a dispersant, a carbon nanotube slurry, a binder and a solvent, and then ground to obtain black liquor; The black liquor is dried and then carbonized at high temperature in an inert atmosphere to obtain a hard carbon composite material with high conductivity.
2. The preparation method according to claim 1, characterized in that: The hard carbon precursor includes at least one of a biomass-based precursor, a polymer-based precursor, and a coal-based precursor; and / or, the binder comprises at least one of a biomass-based binder and a polymer-based binder; Preferably, the polymer-based precursor includes a resin-based precursor; more preferably, the resin-based precursor includes at least one of a phenolic resin and an epoxy resin precursor; Preferably, the coal-based precursor comprises at least one of anthracite, coal tar pitch and lignite; Preferably, the biomass-based precursor comprises at least one of a biological precursor, a sugar-based precursor and a starch-based precursor.
3. The preparation method according to claim 1, characterized in that: The pre-oxidation temperature is 150°C to 280°C, and the pre-oxidation time is 6h to 12h; Preferably, the pre-oxidation temperature is 220° C. and the pre-oxidation time is 12 h.
4. The preparation method according to claim 1, characterized in that: The pre-carbonization temperature is 500°C to 900°C, and the pre-carbonization time is 1h to 6h; Preferably, the pre-carbonization temperature is 800° C. and the pre-carbonization time is 3 h.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the pre-carbonized precursor, the dispersant, the carbon nanotube slurry and the binder is (95-99):(0.5-1):(0.5-5):(0.5-5).
6. The preparation method according to claim 1, characterized in that: The grinding speed is 700 rpm to 1600 rpm; the grinding time is 0.2 h to 3 h; Preferably, the grinding speed is 1200 rpm and the grinding time is 0.5 h.
7. The preparation method according to claim 1, characterized in that: The drying method includes at least one of freeze drying, spray drying, fluidized bed drying and flash drying; Preferably, the drying method is freeze-drying.
8. The preparation method according to claim 1, characterized in that: The temperature of high temperature carbonization is 1000℃~1600℃, and the time of high temperature carbonization is 1h~6h; Preferably, the temperature of high-temperature carbonization is 1300° C., and the time of high-temperature carbonization is 3 hours.
9. A highly conductive hard carbon composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
10. Use of the highly conductive hard carbon composite material according to claim 9 in supercapacitors, batteries or electromagnetic shielding materials.
Citation Information
Cited By
Sodium-ion battery hard carbon material and preparation method thereof
CN122380342A